Effect of distillers dried grains with solubles diet supplemented with rumen‐protected lysine and methionine on milk production and milk amino acids in the lactating cow. (17th June 2013) - Li, Wenbo; Chang, Qifa; Liu, Gang; Shan, Anshan; Li, Feng
<x xml:space="preserve">Abstract</x> This study was to quantify the milk protein and amino acids (AA) in response to rumen‐protected lysine (Lys) and methionine (Met) supplementation in dairy cows fed distillers dried grains with solubles (DDGS) diet. Forty cows were divided into five dietary treatments: soybean meal diet (SM), DDGS diet and DDGS diets with 40 g/day Lys (DL), 20 g/ day Met dry matter (DM) and 20 g/ day Met plus 40 g/ day Lys (DLM), separately. Compared with SM, DL and DM groups, DLM group increased milk yield, 4% fat‐corrected milk, energy‐corrected milk yield and protein in milk. DDGS treatments increased total AA and the essential AA in milk. Results indicated that dietary DDGS increased intestinal supplies of Lys and Met.